Pediatric Computed Tomography Dose Optimization Strategies: A Literature Review - Al Mahrooqi, K.M.S.; Ng, Curtise Kin Cheung; Sun, Zhonghua (Elsevier Inc., 2015)
Introduction: Computed tomography (CT) dose optimization is an important issue in radiography because CT is the largest contributor to medical radiation dose and its use is increasing. However, CT dose optimization for pediatric patients could be more challenging than their adult counterparts. The purpose of this literature review was to identify and discuss the current pediatric CT dose saving techniques. Optimized pediatric protocols were also proposed. Methods: A comprehensive literature search was conducted using the Medline, ProQuest Health and Medical Complete, PubMed, ScienceDirect, Scopus, Springer Link, and Web of Science databases and the keywords CT, pediatric, optimization, protocol, and radiation dose to identify articles focusing on pediatric CT dose optimization strategies published between 2004 and 2014. Results and Summary: Seventy-seven articles were identified in the literature search. Strategies for optimizing a range of scan parameters and technical considerations including tube voltage and current, iterative reconstruction, diagnostic reference levels, bowtie filters, scout view, pitch, scan collimation and time, overscanning, and overbeaming for pediatric patients with different ages and body sizes and compositions were discussed. An example of optimized pediatric protocols specific to age and body size for the 64-slice CT scanners was devised. It is expected that this example could provide medical radiation technologists, radiologists, and medical physicists with ideas to optimize their pediatric protocols.